Auditing fetal nasal bone images in the first trimester of pregnancy: results from a peer review program. (1st September 2016) - Palermo, Fernanda Gasparin; Albuquerque, Débora de Paula Soares de Medeiros; Martins, Wellington P.; Araujo Júnior, Edward; Bruns, Rafael Frederico
Abstract: Objective : To establish a structured review process to facilitate the identification of the fetal nasal bone (NB) in the first trimester ultrasound scan to improve the quality images. Methods : We conducted a retrospective observational study in fetal NB images obtained during ultrasound exams of singleton pregnancies that underwent first trimester screening (crown-rump length 45–84 mm). When the images were obtained the examiner was not aware of the study. Audit was conducted by an examiner according criteria established by the Fetal Medicine Foundation. Fetal NB images were assessed regarding adequate magnification, mid-sagittal view and transducer held parallel to the direction of the nose. The transvaginal and transabdominal as well as anterior and posterior fetal back groups were compared using χ 2 test. Results : We considered 874 fetal NB images for auditing. Fetal NB was considered present in 865 images (99%). During the audit process, we identified 72 (8.2%) cases of disagreement between examiner and auditor assessments. Disagreement was higher when image quality was poor (62 cases = 7%). Transvaginal approach performed better in the following criteria: adequate magnification ( p  < 0.001), midline ( p  < 0.001) and completely adequate ( p  < 0.001). Conclusion : A peer reviewed audit program for fetal NB is feasible in a clinical scenario. Image quality appears to play an important role in compliance to image standards audited and in agreement between examiner and auditor.